2008
DOI: 10.1074/jbc.m706749200
|View full text |Cite
|
Sign up to set email alerts
|

A Regulatory Domain in the N Terminus of Tryptophan Hydroxylase 2 Controls Enzyme Expression

Abstract: Serotonin is involved in a variety of physiological processes in the central nervous system and the periphery. As the rate-limiting enzyme in serotonin synthesis, tryptophan hydroxylase plays an important role in modulating these processes. Of the two variants of tryptophan hydroxylase, tryptophan hydroxylase 2 (TPH2) is expressed predominantly in the central nervous system, whereas tryptophan hydroxylase 1 (TPH1) is expressed mostly in peripheral tissues. Although the two enzymes share considerable sequence h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 50 publications
(68 reference statements)
0
44
0
Order By: Relevance
“…serine-/threonine-phosphorylated motifs that lead in turn to activity changes in bound ligands, altered associations of bound ligands with other cellular components, and changes in intracellular localization of 14-3-3-bound cargo (37). Of major importance to our finding of significantly reduced 14-3-3 isoforms in the medullary 5-HT system in SIDS is their key role in TPH2 modulation (35).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…serine-/threonine-phosphorylated motifs that lead in turn to activity changes in bound ligands, altered associations of bound ligands with other cellular components, and changes in intracellular localization of 14-3-3-bound cargo (37). Of major importance to our finding of significantly reduced 14-3-3 isoforms in the medullary 5-HT system in SIDS is their key role in TPH2 modulation (35).…”
Section: Discussionmentioning
confidence: 57%
“…The remarkable stability of 14-3-3 proteins after death is likely a result of their highly compact well-folded structure (37). Moreover, a study of postmortem changes in proteins in a rat model indicate that 14-3-3 levels increase after 48 h (52), rather than decrease, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that this domain is associated with an inhibitory effect on TPH2 activity [63] . Other studies reported a negative effect of this domain on translational efficiency, stability and solubility of TPH2 compared to tyrosine hydroxylase and PAH [180][181][182][183] .…”
Section: Pharmacological Targeting Of Tph2mentioning
confidence: 99%
“…The additional sequences in TH and TPH2 (Fig. 1), which include the phosphorylation-targeted Ser 19 (17,19), most probably constitute functional domains in the neuronal hydroxylases, as recently suggested for the N-terminal sequence in TPH2 (59). The 43-residue N-terminal region of TH was used in this work to investigate determinants for binding of this functional domain to membranes and 14-3-3 proteins.…”
Section: A 14-3-3-interacting N-terminal Domain In Hth1; Effect Ofmentioning
confidence: 99%